PENGARUH FINANCIAL DISTRESS, FIRM SIZE, AUDIT FEE DAN UKURAN KANTOR AKUNTAN PUBLIK (KAP) TERHADAP KUALITAS AUDIT (Studi Empiris pada Perusahaan BUMN yang Terdaftar di Bursa Efek Indonesia Periode 2020-2024) - Hidayat, Wahyu; Puspa Arum, Enggar Diah; Tiswiyanti, Wiwik (Komunitas Manajemen Kompetitif, 2026)
This study aims to analyze the effect of financial distress, firm size, audit fees, and Public Accounting Firm (KAP) size on audit quality in State-Owned Enterprises (BUMN) listed on the Indonesia Stock Exchange for the 2020–2024 period. The study uses a quantitative approach with multiple linear regression analysis and data processing using SPSS version 30. The research sample consists of 100 observations sourced from the company's annual reports and financial statements. The results of simultaneous tests indicate that financial distress, firm size, audit fees, and KAP size together have a significant effect on audit quality. Partially, the test results indicate that financial distress has a negative and significant effect on audit quality, meaning that the higher the level of financial distress of a company, the lower the audit quality tends to be. Meanwhile, firm size, audit fees, and KAP size do not have a significant effect on audit quality. This finding indicates that company size, audit fees, or KAP classification are not the main determinants of audit quality